Diabetes Mellitus and Its Associated Complications: An introduction - Akram, Muhammad; Laila, Umme; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
Diabetes is a long-term metabolic condition that affects the kidney, liver, heart, eyes, and other body parts. It causes an imbalance in metabolism. Other factors, such as medications and modern living, also have an impact on it. By treating this illness early, we can prevent it. This summary covers a number of different types of diabetes. The fatality rate from diabetes mellitus is increasing on a global scale. Numerous detrimental behaviors, including alcohol use, a sedentary lifestyle, obesity, and a lack of physical activity, further raised the risk of this disease. Numerous issues related to diabetes mellitus are also covered, such as diabetic neuropathy, diabetic cardiomyopathy, diabetic retinopathy, and diabetic nephropathy.